COVID 19-Corona Virus Pandemic Disease: Effect on Human Life - Sampurna Nand Mehta, Dr. Ritu Bhattacharyya, Pooja Tiwari, Tripurari Jha (International Journal of Advanced Science and Technology, 2020)
The beginning of the year new 2020 was really a painful and tough one for the whole world. The whole world was badly derailed and shocked by  the unexpected entry of Novel CORONA Virus in the beginning of the year. Disease pneumonia of unknown cause named Novel coronavirus was first detected in Wuhan, Hubei Province, China and reported to WHO Country Office in China on 31 December 2019. The outbreak was declared a Public Health Emergency of International Concern on 30 January 2020. On 11 February 2020, WHO announced a name for the new coronavirus disease: COVID-19. It was the beginning of Corona virus which gradually spread across the Globe within few days. In India, the first case of corona virus was detected on 31st January 2020 in Kerala when two Indian students were returned from China. Currently the world is fighting and struggling to control the effects of corona virus. This disease has been declared as Pandemic disease. The current situation (17th April 2020) in developed countries is really pathetic where this virus is spreading with lots of casualty and diseased. It is badly affected in countries like America, Spain, Italy, China, France, Germany, UK, Russia, Canada, Belgium and many more. As per Global report[1] on it’s affect there are 2218580 cases of cornovirus detected across the world, out of which 151964 died and 566326 recovered. The similar situation was in India in the beginning of March 2020. The Indian Govt has taken various steps to stop the spread of this pandemic across the country. The Indian government has announced a number of preventive measures to minimise the entry and spread of coronavirus. The Indian government has announced a number of preventive measures to minimise the entry and spread of coronavirus. A 21-days lock-down across the country was imposed from 26 March to 14 April to curb the spread of the coronavirus pandemic which further extended till 3rd May 2020.This study is to find the facts and highlights on the affects of the cornovirus infection. It also reveals to analyse the affects of Lock Down on Human Life which was imposed by Indian Govt to stop the spread of this virus. The study has been taken for the period 21st March 2020 to 22nd  April 2020. The sample size of 177 has been randomly selected from Mumbai, Navi Mumbai, Thane and Palghar districts.